Subacute osteomyelitis masquerading as primary bone Sarcoma: Report of Six cases - Dhanoa, A.; Singh, V.A. (Mary Ann Liebert, 2010)
Background: We report a series of six immunocompetent patients who were believed initially to have primary bone sarcomas, but turned out to have subacute osteomyelitis. Methods: Case report and review of relevant literature. Results: All our patients were treated with antibiotics and recovered fully from the infection. Only one patient had a recurrence with the same offending microorganism, which resolved after a longer period of intravenous antibiotic. Conclusions: Subacute osteomyelitis and bone tumors can be similar in presentation, and the key to proper diagnosis is histopathological and microbiological confirmation in biopsy specimens.